Concentration, Distribution of DDT and Malathion in Soil Water, Plant and Fishes in Rajnandgaon, India - THETWAR, L.K.; SARWAY, P.K.; GUPTA, SANGEETA; TANDON, R.C.; DEWANGAN, H.S.; TRIPATHI, N.K.; Augar, M.R. (Asian Journal of Chemistry, 2010)
Rajnandgaon is thickly populated district headquarter with various industries encompassing the agricultural lands. Pesticides like DDT and malathion are employed in agricultural rural and urban areas. Industrialization increases the concentration of DDT, malathion, lead and cadmium. These are nonbiodegradable in nature. In most of the samples these have been found to show exceedingly high concentration as compared to the tolerance limit as recommended by WHO/FAO.